Performing by the Book? (Leuven University Press, 2024)
The challenges and limits for musicians dealing with texts. To perform a musical score implies the transformation of a symbolically coded text into vibrant sound. In Performing by the Book? a carefully selected cadre of artist-researchers dissects this delicate act in critical ways. Offering first-hand insights into the notational, structural and interpretative challenges faced by musicians in dealing with texts of all kinds, the chapters traverse the spectrum between the Middle Ages and the age of Stockhausen. In a harmonious blend of scholarly allure and individual artistry, free from academic obfuscation, the contributors keep a keen eye on the limits of interpretation, both in terms of the interpretative process itself and of the balance between textual faithfulness and artistic autonomy. This comprehensive volume is an indispensable guide for everyone interested in the relationship between musical performance and texts.